Therapeutic implication of coenzyme Q10 during statin therapy: pros and cons - Mir-Jamal Hosseini; Afshin Mohammadi-bardbori (Shiraz University of Medical Sciences, 2015)
Coenzyme Q10 (CoQ10) is a vitamin-like substance, and a natural intermediate of electron transport chain (ETC) of mitochondria which can accepts and donates electrons from complex I and complex II. CoQ10 shares a biosynthetic pathway with cholesterol and dolichol thus it can be a potential target of the widely available lipid-lowering drugs. The lipid lowering drugs such as statins, are widely administered to individuals who have high cholesterol levels. This article reviews the a) clinical benefits of CoQ10 b) association between administration of statin and CoQ10 deficiency and c) involvement of CoQ10 in statin-associated myopathy.